Mitigating head motion artifact in functional connectivity MRI. Issue 12 (December 2018) - Ciric, Rastko; Rosen, Adon; Erus, Guray; Cieslak, Matthew; Adebimpe, Azeez; Cook, Philip; Bassett, Danielle; Davatzikos, Christos; Wolf, Daniel; Satterthwaite, Theodore
Abstract Participant motion during functional magnetic resonance image (fMRI) acquisition produces spurious signal fluctuations that can confound measures of functional connectivity. Without mitigation, motion artifact can bias statistical inferences about relationships between connectivity and individual differences. To counteract motion artifact, this protocol describes the implementation of a validated, high-performance denoising strategy that combines a set of model features, including physiological signals, motion estimates, and mathematical expansions, to target both widespread and focal effects of subject movement. This protocol can be used to reduce motion-related variance to near zero in studies of functional connectivity, providing up to a 100-fold improvement over minimal-processing approaches in large datasets. Image denoising requires 40 min to 4 h of computing per image, depending on model specifications and data dimensionality. The protocol additionally includes instructions for assessing the performance of a denoising strategy. Associated software implements all denoising and diagnostic procedures, using a combination of established image-processing libraries and the eXtensible Connectivity Pipeline (XCP) software. Ciric et al. describe a protocol for the removal of motion artifacts from functional MRI data. They introduce a software package that implements common denoising protocols and provides tools for assessing the efficacy of denoising.